2016
DOI: 10.1016/j.orl.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

A logarithmic approximation for polymatroid congestion games

Abstract: We study the problem of computing a social optimum (minimum cost solution) in polymatroid congestion games, where the strategy space of every player consists of the set of vectors in a playerspecific integral polymatroid base polyhedron defined on the ground set of resources. For general non-decreasing cost functions we devise an H rk -approximation algorithm, where rk is the sum of the ranks of the player-specific polymatroids and H rk denotes the rk-th harmonic number. The main idea of our algorithm is to it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Approximation algorithms. A number of polynomial time algorithms have been proposed for approximating the minimum social cost in congestion games and their network counterpart as discussed in [2,30,41] and references therein. The best known approximation is due to Makarychev and Sviridenko [41] who use randomization to round the solution of a natural linear programming relaxation.…”
Section: Further Related Workmentioning
confidence: 99%
“…Approximation algorithms. A number of polynomial time algorithms have been proposed for approximating the minimum social cost in congestion games and their network counterpart as discussed in [2,30,41] and references therein. The best known approximation is due to Makarychev and Sviridenko [41] who use randomization to round the solution of a natural linear programming relaxation.…”
Section: Further Related Workmentioning
confidence: 99%
“…The interface between Operations Research and Game Theory is attracting much attention nowadays. Examples are (PPAD) computational complexity of Nash equilibria (see [25], [26], [22], [7], [29] and [8]), price of anarchy (see [28], [6]), congestion games (see [17], [16], [18] and [19]) and manufacturer-retailer problems (see [9] and [3]).…”
Section: Related Literaturementioning
confidence: 99%
“…They also showed that the matroid property is the maximal property that gives rise to a pure Nash equilibrium, that is, for any strategy space not satisfying the matroid property, there is an instance of a weighted congestion game not having a pure Nash equilibrium. Integral polymatroid congestion games, a generalization of matroid congestion games, were later introduced in Harks, Klimm and Peis [15] (see also [16]). In addition, polymatroid theory was recently used in the context of nonatomic congestion games, where it is shown that matroid set systems are immune to the Braess paradox, see Fujishige et al [12].…”
Section: Further Related Workmentioning
confidence: 99%